Certificiranje slovenščine kot drugega/tujega jezika - Ferbežar, Ina (Jezik in slovstvo, 2004)
Certificates of Slovene as a second language have been issued in Slovenia ever since its independence. Considering that in recent years, assessment of national langages has been one of the most topical issues within Europe language policy, this topic has been addressed quite seriously also as the Centre for Slovene as a second/foreign language or, to be more precise, in its assessment centre. The article elucidates some historical facts and reasons for the introduction of certificates of SLovene as a foreign language in Slovenia, shows trends and perspectives in this field, and tries to offer some answers to questions concerning the assessment of linguistic knowledge in general.
Keywords: Slovene; slovenščina; slovenščina kot drugi ali tuji jezik; jezikovna politika; preverjanje znanja